2011
DOI: 10.1590/s1413-35552011000600006
|View full text |Cite
|
Sign up to set email alerts
|

Análise da concordância entre instrumentos de avaliação do equilíbrio corporal em idosos

Abstract: Background: The diagnosis of clinical parameters associated with falls in the elderly has become a major challenge for the scientific community. Despite the existence of several tools aiming to assess body balance in the elderly, it is still scarce the number of studies that have investigated and discussed the agreement between different methods. Objective: To analyze the correlation between tests used to assess the body balance in the elderly. Methods: This was a cross-sectional, observational study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
56

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 21 publications
1
30
0
56
Order By: Relevance
“…The usefulness of the BBS score for the assessment of functional balance has been confirmed in research studies and in clinical practice based on the extensive analysis of its measurement properties, which were found to be reliable 19,20 . In COPD patients, Beauchamp et al 29 demonstrated differences in the BBS score between fallers and non-fallers (45.2±5.40 vs. 48.8±5; p=0.042).…”
Section: Variablesmentioning
confidence: 87%
See 1 more Smart Citation
“…The usefulness of the BBS score for the assessment of functional balance has been confirmed in research studies and in clinical practice based on the extensive analysis of its measurement properties, which were found to be reliable 19,20 . In COPD patients, Beauchamp et al 29 demonstrated differences in the BBS score between fallers and non-fallers (45.2±5.40 vs. 48.8±5; p=0.042).…”
Section: Variablesmentioning
confidence: 87%
“…The BBS examines balance by using different standardized positions and actions related to 14 daily life items. The items are scored according to the time that the body position can be maintained and the distance at which the arm is capable of reaching forward 19,20 . Each item has an ordinal scale of five alternatives, ranging from 0 to 4 points.…”
Section: Measurementsmentioning
confidence: 99%
“…Aliado ao fato, quedas elevam os custos do atendimento ambulatorial e dos serviços de hospitalização 5 . Diante disso, cresce o interesse da ciência sobre fatores associados ao risco de queda de idosos 6 , assim como de instrumentos que qualifiquem a avaliação clínica do equilíbrio 7 .…”
Section: Introductionunclassified
“…Isso significa dizer que quedas são eventos multifatoriais. De forma geral, seus fatores de risco são conhecidos, contudo, suas inter-relações, assim como o peso de cada fator ainda carece de maior entendimento 7,15,16 . Sendo assim, a avaliação do déficit do equilíbrio necessita de instrumentos abrangentes e confiáveis 17 .…”
Section: Introductionunclassified
“…Cerca de 30% a 40% dos idosos, com idade acima de 65 anos, podem apresentar alterações na marcha que facilitam as quedas, que são responsáveis por taxas significativas de atendimentos emergenciais e de hospitalização do idoso, 6% e 10% respectivamente (4) , além de, ocasionarem alterações funcionais, redução da autoestima e do domínio do esquema corporal, sendo, por isso, um fator de grande relevância epidemiologia, social e econômica em todo o mundo (5)(6) . A imagem do corpo ou a consciência que o ser humano tem de sua presença corporizada supera as fronteiras da anatomia.…”
Section: Introductionunclassified